Neural oscillations associated with auditory duration maintenance in working memory - Xiaolin Yu (Nature Portfolio, 2017)
Abstract The neural representation of auditory duration remains unknown. Here, we used electroencephalogram (EEG) recordings to investigate neural oscillations during the maintenance of auditory duration in working memory (WM). EEG analyses indicated that the auditory duration length was not associated with changes in the theta band amplitude, whereas the alpha band amplitudes during 3-s and 4-s auditory duration conditions were lower than during the 1-s and 2-s conditions. Moreover, the alpha band amplitude and accuracy were positively correlated in the 2-s duration condition. We also found that the neural representation of auditory duration is segmented, with a critical threshold point of approximately 2 s, which is shorter than that for visual duration (3 s). The results emphasised the involvement of the alpha band in auditory duration maintenance in WM. Our study’s findings indicate that different internal representations of auditory durations are maintained in WM below and above 2 s from the perspective of electrophysiology. Additionally, the critical threshold point is related to the sensory modality of duration.